African Entrepreneurs’ Perceptions on the Mentoring Provided by a Cross-cultural Professional Development Experience: Implications for Future Program - Lisa K. Taylor; M. Craig Edwards; Marshall A. Baker; Craig E. Watters; James A. Rutledge (Journal of International Agricultural and Extension Education, 2020)
We conducted a multicase investigation to assess the impacts of a cross-cultural exchange program on Entrepreneur Fellows from Kenya, South Africa, and Uganda (8 women; 14 men) after they had returned home from the United States. Our assessment included the mentoring aspect of the program. Six questions and related probes guided semi-structured interviews with the 22 Fellows, the study’s quintain. The lead researcher transcribed the study’s interviews and verified accuracy and trustworthiness by sending her transcriptions to the Fellows for verification. Findings derived from the interviews or cases crystallized as themes representative of the quintain. The emergent themes, which included mentoring, inspired two theoretical lenses to guide our interpretation of the Fellows’ experiences: human capital theory and theory of planned behavior. Recommendations for practice include additional training of entrepreneur mentors and suggestions to facilitate high-quality field experiences. Additional research examining participants’ views about mentoring – protégés and their mentors – as an integral component of entrepreneurial training in cross-cultural settings, and how that can be improved, would likely enhance the learning outcomes of similar programs.
Keywords: entrepreneurship; international exchanges; mentoring; professional development